Energy dissipation channels in the adsorption of N on Ag(111) - Martin Gondre, L. (2012)
We theoretically study the competition between different energy dissipation channels in the adsorption of N atoms on Ag(1 1 1) surfaces. The three-dimensional potential energy surface that describes the interaction between the N atoms and the metal surface is built from density functional theory calculations. Classical dynamics simulations are subsequently performed to evaluate the adsorption probabilities. The contribution of electron?hole pairs excited in the surface during the adsorption process is included in the simulation by an electronic friction coefficient. Phonon excitations are also considered through the Generalized Langevin Oscillator model. We show that the role of the two channels during the adsorption dynamics is very different: phonons are responsible for determining the adsorption probability but electronic excitations are relevant at a later stage to fix the N atoms to the adsorption positions. We conclude that a theoretical model that intrinsically combines both energy dissipation channels is necessary to properly describe the full dynamics of the process.